The balancing act of establishing a policy agenda: Conceptualizing and measuring drivers of issue prioritization within interest groups. Issue 2 (2nd May 2017) - Halpin, Darren R.; Fraussen, Bert; Nownes, Anthony J.
Abstract : Interest groups are important intermediaries in Western democracies, with the potential to offer political linkage and form a bridge between the concerns of citizens and the agendas of political elites. While we know an increasing amount about the issue‐based activity of groups, we only have a limited understanding about how they selected these issues to work on. In this article, we examine the process of agenda setting within groups. In particular, we address challenges of conceptualization and measurement. Through a thorough review of the group literature, we identify five main factors that are hypothesized to drive issue prioritization. We operationalize items to tap these factors and then empirically assess this theoretical model relying on data from a survey of national interest groups in Australia. Our findings, from a confirmatory factor analysis, provide support for the multidimensional nature of agenda setting. We discuss how this provides a firm conceptual and methodological foundation for future work examining how groups establish their policy agenda.